Genes expressed in coronary thrombi are associated with ischemic time in patients with acute myocardial infarction. Issue 2 (February 2015) - Helseth, R.; Seljeflot, I.; Opstad, T.; Solheim, S.; Freynhofer, M.; Arnesen, H.; Huber, K.; Weiss, T.
Abstract Introduction Reports on the content of aspirated coronary thrombi have until now mainly focused on cellular components. We investigated the genetic expression of selected mediators and proteases actively involved in the pathophysiological process of acute myocardial infarction in aspirated coronary thrombi. Materials and Methods In this cross-sectional study, RNA from coronary thrombi in 67 subjects with acute myocardial infarction was isolated. Gene expression arrays of selected markers were performed by RT-PCR with relative quantification. Results Twenty of 22 markers were expressed in > 50% of the samples. The relative quantification of P-selectin correlated negatively to total ischemic time (p = 0.01), while genes related to fibrinolysis (t-PA, u-PA, PAI-1), inflammation (PTX3, CXCL9, MCP-1, IL18, TNFα) and plaque instability (MMP-2 and TIMP-1) correlated positively to total ischemic time (all < 0.05). Long ischemic time (> 4.0 hours) associated with a relative reduction in the expression of P-selectin and a relative increase in the expression of t-PA, u-PA, PAI-1, PTX3, CXCL9, MCP-1, IL-18, TNFα, MMP-2 and TIMP-1. The presence of type 2 diabetes associated with 3.2-fold increased PAI-1 expression (adjusted p = 0.033), while the presence of hypertension associated with about 50% reduction of IL-8 and TIMP-1. Smoking and overweight did not affect any markers. Conclusions The gene expression profile from coronary thrombi differed according to ischemic time, shown by reduced content of platelet markers and increased content of fibrinolytic, inflammatory and plaque instability mediators over time. Patients with type 2 diabetes showed increased expression of PAI-1, indicative of reduced fibrinolysis.